SIFO 1990: EC-opinion - Swedish Institute of Public Opinion Research; Swedish Employers´ Confederation (Swedish Institute of Public Opinion Research, 1994)
This study was carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the Swedish Employers' Confederation. Questions were asked about interest in following what happens within the EC and Eastern Europe respectively; opinion on the development of standard of living, social welfare, and number of jobs within the country if Sweden joined the EC; attitude toward the free labour market within the EC; and to how a Swedish EC-membership would affect fields such as the environmental protection, working environment, and the security of the country. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union and income.

Denna studie gjordes av Svenska institutet för opinionsundersökningar (SIFO) på begäran av Svenska Arbetsgivarföreningen. Frågor ställdes om huruvida intresse fanns för att följa vad som händer inom respektive EG och öst Europa, om åsikten om utvecklingen av levnadsstandarden, social välfärd och antalet jobb inom Sverige om Sverige gick med i EG; inställningen till den fria marknaden inom EG och hur ett svenskt medlemskap i EG skulle påverkas vad gäller miljöskydd, arbetsmiljön och rikets säkerhet. Bakgrundsvariabler inkluderar information om kön, bostadsort, ålder, svenskt medborgarskap, yrke, privat eller offentlig sektor, medlemskap i fackförening och inkomst.
SIFO 1990: EG-opinionen
Keywords: INTERNAL POLITICS; INRIKESPOLITIK; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap